Intramuscular Brown Fat Activation Decreases Muscle Atrophy and Fatty Infiltration and Improves Gait After Delayed Rotator Cuff Repair in Mice. Issue 7 (June 2020) - Wang, Zili; Liu, Xuhui; Jiang, Kunqi; Kim, Hubert; Kajimura, Shingo; Feeley, Brian T.
Background: Successful repair of large and massive rotator cuff (RC) tears remains a challenge at least partially because of secondary muscle atrophy and fatty infiltration. β3 Adrenergic agonists are a group of drugs that promote fat resorption through "white fat browning" of intramuscular stem cells. Purpose: To test the role of a β3 adrenergic receptor agonist, amibegron, in improving muscle quality and forelimb function in a delayed RC repair model via promoting brown/beige adipose tissue activation. Study Design: Controlled laboratory study. Methods: Three-month-old PDGFRα-GFP reporter mice, wild type C57BL/6J mice, and uncoupling protein 1 (UCP-1) knockout mice underwent unilateral supraspinatus tendon transection with a 6-week delayed tendon repair. Animals with sham surgery served as controls. Amibegron was given either immediately after tendon transection or after repair. Gait analysis was conducted to measure forelimb function at 6 weeks after tendon repair. Animals were sacrificed at 6 weeks after repair. Supraspinatus muscles were harvested and analyzed histologically. Reverse transcription polymerase chain reaction was performed to quantify gene expression related to atrophy, fibrosis, and fatty infiltration. Results: Histology of PDGFRα reporter mice showed significantly increased UCP-1 expression, suggesting white fat browning in muscle after RC repair. As administered either immediately after tendon transection or after tendon repair, amibegron significantly reduced muscle atrophy and fatty infiltration and resumed normal upper extremity gait in wild type mice. However, the effect of amibegron was not present in UCP-1 knockout mice, suggesting that the effect of amibegron in treating RC muscle atrophy and fatty infiltration is through a UCP 1–dependent mechanism. Conclusion: Amibegron reduced muscle atrophy and fatty infiltration and improved forelimb function after delayed RC repair through a UCP 1–dependent mechanism. This may be an effective clinical treatment strategy for patients to improve muscle quality after RC repair. Clinical Relevance: β3 Adrenergic agonists may serve as a new pharmacologic modality to treat RC muscle atrophy and fatty infiltration to improve clinical outcome of RC repair.